Diverse Lineages of Candida albicans Live on Old Oaks. Issue 1 (21st November 2018) - Bensasson, Douda; Dicks, Jo; Ludwig, John M; Bond, Christopher J; Elliston, Adam; Roberts, Ian N; James, Stephen A
Abstract: Most humans are inhabited by the yeast Candida albicans at some point. While largely harmless, it is the most common cause of yeast infections. Though previously unclear whether the yeast can live outside of warm-blooded animals, Bensasson et al. .... The human pathogen Candida albicans is considered an obligate commensal of animals, yet it is occasionally isolated from trees, shrubs, and grass. We generated genome sequence data for three strains of C. albicans that we isolated from oak trees in an ancient wood pasture, and compared these to the genomes of over 200 clinical strains. C. albicans strains from oak are similar to clinical C. albicans in that they are predominantly diploid and can become homozygous at the mating locus through whole-chromosome loss of heterozygosity. Oak strains differed from clinical strains in showing slightly higher levels of heterozygosity genome-wide. Using phylogenomic analyses and in silico chromosome painting, we show that each oak strain is more closely related to strains from humans and other animals than to strains from other oaks. The high genetic diversity of C. albicans from old oaks shows that they can live in this environment for extended periods of time.